ANALISIS PENGARUH ARUS KAS TERHADAPPROFITABILITAS PADA PT MAYORA INDAH TBK - Hendro sasongko; Dewi apriani (Universitas Pakuan, 2016)
This study aims to determine whether the cash flows either partially or simultaneously affect the profitability (ROA) at PT Mayora Indah Tbk 2010-2014. Research on the cash flow analysis of the effect on profitability. This type of research is a correlational study with a total sample of 10 per six months in the financial statements at PT Mayora Indah Tbk during the period 2010-2014. The process of data analysis done first is the classic assumption test before hypothesis test. Statistical method used is multiple linear regression using SPSS. The results showed that cash flow is comprised of operating cash flow, cash flow investing and financing cash flows simultaneously there is no significant effect on profitability (ROA). Partial test results show that the variable operating cash flow, cash flow investing and financing cash flow is not a significant influence on profitability (ROA).Keywords: operating cash flow, investing cash flows, financing cash flow and profitability (ROA).